2018
DOI: 10.1149/2.0831810jes
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Copper(II)–Lactate Complexes in Cu2O Electrodeposition Baths: Deprotonation of the α-Hydroxyl Group in Highly Concentrated Alkaline Solution

Abstract: Unveiling dissolved species in electrodeposition baths helps our understanding of electrodeposition behavior, such as growth orientation. A highly concentrated aqueous alkaline copper(II)-lactate solution is used for the electrodeposition of copper(I) oxide (Cu 2 O) thin films with <111> orientations; the semiconductor properties of these films facilitate their use in solar-cell materials, photocathodes, and photocatalysts. However, the dissolved species, presumably copper(II)-lactate complexes, cannot be dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…This work precipitates at pH > 8.0, which is inconsistent with the experimental results. In contrast, we also confirmed the formation of the Cu(OH) 2 precipitate during the dilution of 0.4 M copper(II)-3.0 M lactate solution with deionized water above pH 8.0, 18 which corresponded with the data shown in Figure 7b. These results indicated that the reported thermochemical data were insufficient to discuss the concentrated copper(II)-lactate system in the alkaline region.…”
Section: Reactionsupporting
confidence: 87%
See 4 more Smart Citations
“…This work precipitates at pH > 8.0, which is inconsistent with the experimental results. In contrast, we also confirmed the formation of the Cu(OH) 2 precipitate during the dilution of 0.4 M copper(II)-3.0 M lactate solution with deionized water above pH 8.0, 18 which corresponded with the data shown in Figure 7b. These results indicated that the reported thermochemical data were insufficient to discuss the concentrated copper(II)-lactate system in the alkaline region.…”
Section: Reactionsupporting
confidence: 87%
“…Preparation of sample solutions.-For recording the UV-vis absorption spectra, 30 sets of 15-mL aqueous solutions of 0.4 mol dm -3 copper(II)-3.0 M lactate 18 were used as the analytes. Each sample contained 0.06 mol (2.25 g) Cu(ClO 4 ) 2 •6H 2 O (99%, Nacalai Tesque) and 0.045 HL (3.75 mL) (91.1%, Nacalai Tesque).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations